Comprehensive care models for the elderly in the world: Literature review - Placideli, Nádia [UNESP]; Bocchi, Silvia [UNESP] (FapUNIFESP (SciELO), 2021)
Integrative review of national and international literature on models of comprehensive care for the elderly, from six articles analyzed in full and located through systematic searches, in the Lilacs, PubMed, Scopus, CINAHL and Web of Science databases, in the last five years. The results show that there are innovative models for comprehensive care for the elderly, especially in developed countries, focused on long-term care for the frail elderly; all of them emphasize the various challenges for adapting, implementing, and maintaining these models that consider the continuous demands of this population. This research points to the need to build models of comprehensive care that address the several demands of the elderly, integrated with the articulation between health and social services, to advance the promotion of active aging and sustainability over time such proposals. It constitutes an emergency demand for countries with accelerated population aging process, as it is the case in Brazil.
Modelos de atenção integral para idosos no mundo: Revisão da literatura
Keywords: Elderly; Health care for the elderly; Health services for the aged; Integrality; Intersectoriality